Research on Factors Affecting the 3D Jelly Cakes Demand of Hanoi Customers (International Journal of Scientific Research and Management (IJSRM), 2023)
The study analyzes some factors affecting Hanoi consumers’ demand for 3D jelly cake. Based on the theory of commodity demand, the research team conducted a survey and collected answers from 308 consumers on some factors affecting 3D jelly cake demand. The synthesis and analysis of survey data indicated that the demand for 3D jelly cakes of Hanoi consumers is influenced by many factors such as the price of the product, tastes, prices of substitutes, and complementary goods...In addition, the research team also considered the advantages of 3D jelly cake compared to other products, as well as discussed some solutions to stimulate consumer demand with this new and aesthetic product.